2020
DOI: 10.1016/j.envpol.2020.115008
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prenatal urinary bisphenol A level and child cardio-metabolic risk factors: A prospective cohort study

Abstract: Exposure to endocrine disrupting chemicals during the first 1000 days of life may have long-lasting adverse effects on cardio-metabolic risk in later life. This study aimed to examine the associations between maternal prenatal Bisphenol A (BPA) exposure and child cardio-metabolic risk factors at age 2 years in a prospective cohort. During 2012–2013, 218 pregnant women were enrolled at late pregnancy from Shanghai, China. Urinary BPA concentration was measured in prenatal and child 2-year spot urine samples, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…In contrast, in girls, the plasma glucose level was lower (0.26 mmol/L) with moderate prenatal BPA levels; however, the difference was not significant. The study also showed no associations between prenatal BPA exposure and children's body weight, BMI, skinfold thickness, serum lipid levels, or insulin levels in children aged two years old, either for girls or boys [69].…”
Section: Metabolic Effect Of Prenatal Bpa Exposure In Children (Epide...mentioning
confidence: 73%
“…In contrast, in girls, the plasma glucose level was lower (0.26 mmol/L) with moderate prenatal BPA levels; however, the difference was not significant. The study also showed no associations between prenatal BPA exposure and children's body weight, BMI, skinfold thickness, serum lipid levels, or insulin levels in children aged two years old, either for girls or boys [69].…”
Section: Metabolic Effect Of Prenatal Bpa Exposure In Children (Epide...mentioning
confidence: 73%
“…BPA exposure during pre-natal period was associated with increased blood pressure in girls and plasma glucose in boys. 69 Adolescents with polycystic ovary syndrome were found to have significantly higher BPA levels when compared with the control group. 70 …”
Section: Resultsmentioning
confidence: 92%
“…At age 12 and 24 months, weight, length, mid-upper arm circumference (MUAC), and skinfold thickness were measured by study nurses according to the WHO protocol, and described elsewhere [20]. With 70-90% of total adipose tissue located subcutaneously, skinfold thickness can be used to reflect total body fat [21].…”
Section: Child Anthropometric Measuresmentioning
confidence: 99%